2021
DOI: 10.1111/nph.17676
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of lytic polysaccharide monooxygenase by natural plant extracts

Abstract: Lytic polysaccharide monooxygenases (LPMOs) are monocopper enzymes of industrial and biological importance. In particular, LPMOs play important roles in fungal lifestyle. No inhibitors of LPMOs have yet been reported.In this study, a diverse library of 100 plant extracts was screened for LPMO activitymodulating effects. By employing protein crystallography and LC-MS, we successfully identified a natural LPMO inhibitor.Extract screening revealed a significant LPMO inhibition by methanolic extract of Cinnamomum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 69 publications
(100 reference statements)
0
14
0
Order By: Relevance
“…Once again, alleviation of LPMO inhibition was successfully achieved with the addition of PEG. In a recent study, a polyphenolic inhibitor from an extract of cinnamon, cinnamtannin B1, was shown to bind to the surface of an LPMO [ 9 ]. In this study, TaAA9A was reported to have lower susceptibility to inhibition by the cinnamon extract during PASC degradation, in contrast to TfLPMO10A, which showed the highest.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Once again, alleviation of LPMO inhibition was successfully achieved with the addition of PEG. In a recent study, a polyphenolic inhibitor from an extract of cinnamon, cinnamtannin B1, was shown to bind to the surface of an LPMO [ 9 ]. In this study, TaAA9A was reported to have lower susceptibility to inhibition by the cinnamon extract during PASC degradation, in contrast to TfLPMO10A, which showed the highest.…”
Section: Discussionmentioning
confidence: 99%
“…This co-substrate did not affect TaAA9A activity and inhibition under the tested conditions ( Figure A1 ), which is an indication that Kakishibu inhibition did not stem from potential H 2 O 2 -scavenging properties of the juice. A number of small phenolic compounds were detected in Kakishibu juice ( Table A1 ), among which is the well-known LPMO reductant gallic acid, as well as catechin, taxifolin, and quercetin, which have also been reported as LPMO activators [ 9 ]. The positive effect of complex biomass mixtures has been reported previously, such as TaAA9A activation by pretreated corn stover [ 24 ], as well as activation by pretreated wheat straw for T. reesei and S. marcescens LPMOs [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, this study makes us wonder about the evolutionary relationship, if any, between LPMO‐derived oxidised oligosaccharides and plant cellular receptors (Liu et al ., 2012; Shinya et al ., 2015). Interestingly, we underscore that the secretion of chemicals by the plant could also be used as a means to regulate fungal LPMO activity, as a very recent report has shown that some plant extracts (containing cinnamtannin B1) acted as a potent LPMO inhibitor (Tokin et al ., 2021).…”
Section: Emerging Biological Functionsmentioning
confidence: 99%